Organisational factors promoting the in-house EAP in the Department of Economic Development Environment and Tourism in Limpopo - Spies, Gloudien M. (University of Pretoria, 2018)
The researcher observed in practice that in-house EAP services renders a comprehensive EAP services to the organisations, although there are always factors involved that contribute to the failures and success of the internal EAP’s. EAP is usually a small directorate reporting under human resources and staffed by professionals who are positioned in middle management in an organisation. This study aimed to explore and describe the organisational factors that may promote the in-house EAP in the Department of Economic Development, Environment and Tourism in Limpopo. The study focused specifically on the organisational factors that may play an important role in promoting service delivery of in-house EAP’s by exploring the views of the EAP professionals in the Department under study. The main objectives of the study was to determine which organisational factors may promote an inhouse EAP in the Department of Economic Development, Environment and Tourism in Limpopo. Certain recommendations regarding the way these organisational factors can promote an effective in-house EAP, were also formulated. A qualitative collective case study research design was utilized in order to reach the goal of the study. The population represented EAP professionals in the specific department and a semi-structured interview schedule was used to interview the participants. The empirical findings of the study suggest that factors such as insufficient budget, lack of professionals specifically allocated for EAP services may have a negative impact on the promotion of an in-house EAP. Factors such as availability of approved EAP policies, management support and involvement, financial support, accessibility and location of EAP services, marketing of the EAP services, as well as the appointment of relevant professionals to render EAP services, were recognised as factors that may contribute to the promotion of an in-house EAP at the Department of Economic Development, Environment and Tourism in Limpopo.